Why has mortality in England and Wales been increasing? An iterative demographic analysis - Hiam, L; Dorling, D; Harrison, D; McKee, M (SAGE Publications, 2017)
Objectives To understand why mortality increased in England and Wales in 2015. Design Iterative demographic analysis. Setting England and Wales Participants Population of England and Wales. Main outcome measures Causes and ages at death contributing to life expectancy changes between 2013 and 2015. Results The long-term decline in age-standardised mortality in England and Wales was reversed in 2011. Although there was a small fall in mortality rates between 2013 and 2014, in 2015 we then saw one of the largest increases in deaths in the post-war period. Nonetheless, mortality in 2015 was higher than in any year since 2008. A small decline in life expectancy at birth between 2013 and 2015 was not significant but declines in life expectancy at ages over 60 were. The largest contributors to the observed changes in life expectancy were in those aged over 85 years, with dementias making the greatest contributions in both sexes. However, changes in coding practices and diagnosis of dementia demands caution in interpreting this finding. Conclusions The long-term decline in mortality in England and Wales has reversed, with approximately 30,000 extra deaths compared to what would be expected if the average age-specific death rates in 2006–2014 had continued. These excess deaths are largely in the older population, who are most dependent on health and social care. The major contributor, based on reported causes of death, was dementia but caution was advised in this interpretation. The role of the health and social care system is explored in an accompanying paper.